Nonlinear electric conduction of CCTO/EPDM composites used for reinforced insulation in cable accessory - Li, Zhongyuan; Zhang, Jian; Chen, Shiyu; Liu, Heqian; Wang, Lei; Liang, Jianquan; Zhang, Kexin; Zhang, Peng; Sun, Weifeng (Frontiers in Energy Research, 2023)
Abstract Nonlinear electric conductance of reinforce insulation can homogenize electric field distribution and suppress local electric field distortion inside high voltage direct current cable accessories. To achieve a significant nonlinear electric conductance in ethylene-propylene-diene misch-polymere (EPDM) used for reinforce insulation of cable accessories, the inorganic micron-crystal powder of copper calcium titanate (CCTO) is synthesized by sol-gel method, which is filled into EPDM to prepare 5~15wt%CCTO/EPDM composites by melting blend and hot-press molding methods. Microscopic structure, electric conductivity, DC dielectric breakdown strength and charge trap characteristics of CCTO/EPDM composites are tested to reveal the underlying derivation of electric conduction non-linearity. Scanning electron microscopy and XRD demonstrate that CCTO micron fillers are uniformly dispersed in EPDM matrix. Dielectric breakdown strength of CCTO/EPDM composites gradually decreases with the increase of CCTO content, while persisting qualified for electrical insulation of DC cable accessories. CCTO crystal macron fillers introduce shallower charge traps than the intrinsic charge traps derived from structural defects EPDM matrix, which initiates the percolating conductive channels between charge traps under high electric fields, accounting for the significant non-linearity in the profile of electric current density versus electric field strength. Finite-element simulations and analyses on the electrostatic field in DC cable terminals prove that employing 15wt%CCTO/EPDM composite as reinforce insulation can efficiently homogenize electric field at interface between main insulation and accessory insulation of power cables, which is of great interests to develop insulation materials used for DC cable accessories in severe environments.